A influência da pandemia de covid-19 na percepção do bem-estar financeiro. - Camila Viana Brasil (2022)
Financial well-being can be defined as a state of being of the individual in which he can fulfill his present and future financial commitments, feeling security in his financial future. The objective of the present study is to verify the influence of the Covid-19 pandemic on the financial well-being of Brazilians. The survey was carried out with 591 Brazilian respondents and as a data collection instrument, a structured electronic questionnaire was used, consisting of thirty-nine questions segregated into five blocks, which addressed variables related to four constructs: perceptions of financial situation, financial well-being , financial ignorance, financial education, as well as socioeconomic and demographic aspects. For data analysis, descriptive statistics, t-test and Post Hoc ANOVA and structural equation modeling were applied. The results indicated that the Covid-19 Pandemic negatively influenced the perception of BEF, with an increase in the uncertainties and insecurities of individuals regarding their financial future during the pandemic period, greater pessimism regarding the perceptions of the current family financial situation, as well as for the prospects of the future situation; low level of financial ignorance and high level of financial education. Significant mean differences were identified for the socioeconomic and demographic variables in relation to the four analyzed constructs, except for the age variable, which showed no differences between the groups. It was also found that women and the most financially vulnerable individuals reported the greatest loss of BEF during the pandemic. The perception of the future financial situation is the construct that most impacts the loss of financial well-being during turbulent and stressful periods such as the Covid-19 Pandemic. Finally, the main contribution of the study is the proposition of an integrated model used to measure the change in BEF as a result of the pandemic.